Whole Community Metatranscriptomes and Lipidomes Reveal Diverse Responses Among Antarctic Phytoplankton to Changing Ice Conditions - Bowman, Jeff S.; Van Mooy, Benjamin A. S.; Lowenstein, Daniel P.; Fredricks, Helen F.; Hansel, Colleen M.; Gast, Rebecca; Collins, James R.; Couto, Nicole; Ducklow, Hugh W. (Frontiers in Marine Science, 2021)
The transition from winter to spring represents a major shift in the basal energy source for the Antarctic marine ecosystem from lipids and other sources of stored energy to sunlight. Because sea ice imposes a strong control on the transmission of sunlight into the water column during the polar spring, we hypothesized that the timing of the sea ice retreat influences the timing of the transition from stored energy to photosynthesis. To test the influence of sea ice on water column microbial energy utilization we took advantage of unique sea ice conditions in Arthur Harbor, an embayment near Palmer Station on the western Antarctic Peninsula, during the 2015 spring–summer seasonal transition. Over a 5-week period we sampled water from below land-fast sea ice, in the marginal ice zone at nearby Palmer Station B, and conducted an ice removal experiment with incubations of water collected below the land-fast ice. Whole-community metatranscriptomes were paired with lipidomics to better understand how lipid production and utilization was influenced by light conditions. We identified several different phytoplankton taxa that responded similarly to light by the number of genes up-regulated, and in the transcriptional complexity of this response. We applied a principal components analysis to these data to reduce their dimensionality, revealing that each of these taxa exhibited a strikingly different pattern of gene up-regulation. By correlating the changes in lipid concentration to the first principal component of log fold-change for each taxa we could make predictions about which taxa were associated with different changes in the community lipidome. We found that genes coding for the catabolism of triacylglycerol storage lipids were expressed early on in phytoplankton associated with a Fragilariopsis kerguelensis reference transcriptome. Phytoplankton associated with a Corethron pennatum reference transcriptome occupied an adjacent niche, responding favorably to higher light conditions than F. kerguelensis. Other diatom and dinoflagellate taxa had distinct transcriptional profiles and correlations to lipids, suggesting diverse ecological strategies during the polar winter–spring transition.